The effect of sintering pressure on the wear behavior of bronze (85/15) alloys produced using hip method - Yildiz, T.; Kati, N.; Gur, A. K.; Aba, S. (Sharif Univ Technology, 2021)
In this study, new material was produced using Hot Isostatic Pressing (HIP) method, upon which Co and Ni were added in different proportions into a CuSnbased (85/15) alloy. Considered as its very important advantage, HIP method allows simultaneous application of pressure and temperature during the process. A constant sintering temperature of 800 degrees C, a constant sintering time of 15 min, and two different sintering pressures of 20 and 30 MPa were used. The sintering process was performed in a vacuum after the initial burning process. The produced samples were subjected to various metallographic processes as well as Scanning Electron Microscope (SEM) and Energy Distribution Spectrometer (EDS) analyses. Afterward, a wear test was carried out on the samples. The study investigated the effects of Ni and Co addition and sintering pressure on the wear behavior. It was found that as the amount of Co and the sintering pressure increased, the wear resistance increased. (C) 2021 Sharif University of Technology. All rights reserved.
Keywords: Hot isostatic pressing; CuSn; Microstructure; Wear; Microhardness